Akuntabilitas Program Kemandirian Desa Berbasis Smart village: Studi Kasus Pengelolaan BUMDes Tirta Mandiri - Nurfaisal, Muhammad Dwi; Maulana, Muhammad Akbar; Sari, Inrinofita (Indonesian Journal Publisher, 2024)
This study aims to analyze the accountability of the village independence program in the management of Village-Owned Enterprises (BUMDes). Digital transformation and management innovation in the technology era offer opportunities for BUMDes to optimize the economic function of the village through more transparent, efficient, and participatory governance. This study uses a qualitative approach with a case study method at BUMDes Tirta Mandiri, Ponggok Village, Polanharjo District, Klaten Regency, Central Java Province. The results of the study indicate that the application of the principle of accountability of the village independence program in the management of BUMDes, such as openness of information related to legal certainty, processes, policies, and income generating. This is expected to increase public trust, encourage the sustainability of BUMDes business units, understand problems that occur in society, and improve the quality of life of the community to achieve village independence. In addition, the use of technology in the form of a digital platform in financial management and BUMDes services, especially business units owned such as the tourism sector, building management, village shops, and village study tours allow for integration between accountability and public service innovation. Keywords: BUMDes Management, Accountability, Digital Transformation, Income Generating.